E-Module biology based on rawa danau nature reserve: To improve biodiversity literacy of high school students - Firmansyah, Fahmie; Ramadhan, Rifky Aditya (Universitas Negeri Jakarta, 2025)
Based on data from the World Wide Fund for Nature (WWF) in the Living Planet Report 2022, it was reported that the biodiversity population experienced an average decline of 69% between 1970 and 2018. Therefore, instilling conservation values ​​and biodiversity literacy is critical from an early age to foster knowledge about the environment. This study aims to develop a biodiversity-based Biology E-Module at CARD to improve the biodiversity literacy of high school students. This research method uses a type of development research using the ADDIE model. The ADDIE model stage begins with 1) needs analysis. 2) Design of product specifications and frameworks. 3) development of product design. 4) Implementation of products in the field. 5) evaluate the product and make improvements if necessary. The results of the media and material experts' assessment show that the biology e-module is very feasible. The study results show the average value of students' biodiversity literacy knowledge before and after using this e-module. The average posttest score of 84 is greater than the average pretest score of 70.8 in the ability to understand biodiversity literacy, and based on this, the Biodiversity-Based Biology e-module in the Rawa Danau Nature Reserve effectively increases students' biodiversity literacy.